Influence of Fees, Religiousness, and Service Quality on Customer Interest in Pawn Products at Kuala Simpang - Syafrizal, Muhammad; Rahma, Tri Inda Fadhila; Jannah, Nurul (IAIN Manado, 2025)
The purpose of the research is to examine the factors that influence customers' desire to utilize the services of PT Pegadaian Syariah Kuala Simpang Branch. This study employs a quantitative methodology and uses SPSS version 23 for statistical data analysis. The number of respondents is 100 individuals, and the population consists of all customers who use pawned items (Rahn) at the designated branch. The results of the study indicate that the interest rate variable has a significance level of 0.000, which is less than 0.05, and a t-value of 5.660, which is greater than the t-table value of 1.660. Additionally, the religiosity variable has a significance level of 0.000 < 0.05, and a t-value of 17.252 > 1.660. Similarly, the t-value for the service quality variable is 13.113 > 1.660 with a significance threshold of 0.000 < 0.05. Furthermore, the F-test results show a significance level of 0.004, which is less than 0.05, and an F-value of 659.149, which is greater than the F-table value of a magnitude of 2.699. This result implies that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. With an Adjusted R Square score of 95.2%, the model explains 95.2% of customer interest, with additional factors not included in the regression model affecting the remaining 4.8%.